The Effect of Edelson’s Model in Developing Mathematical Interconnectivity skills and Achievement for Second- Grade Students in Mathematics - Abd Al-Amer, Abbas Naji; Dawod Al-Juboury, Salam Abas (Opción, 2019)
The objective of the research was to identify the effect of the Edelson model in developing the mathematical interpersonal skills of second average grade students in mathematics. To achieve the research objective, the researcher adopted the empirical research method, the empirical design of two parallel groups of pre and post- test in mathematical interdependence. The experiment was applied on a study group consisted of (65) students, the experimental group (33) students, and the control group (32) students from the second aver- age grade students in (Berier intermediate school) of Directorate of Education province of Diyala for the academic year 2018-2019. The research tool was built (Mathematical Interdependence Skills), The Mathematical Interaction Skills Test consisted of (30) thematic paragraphs of multiple choice. The hon- esty of the test has been verified, the difficulty and discrimination coefficients, and the effectiveness of the wrong alternatives were tested. The appropriate statistical means were the (Kyodar Richard) equation, the T-test and Pearson correlation coefficient using the SPSS V.23.0